How Digitalization Enhances Fiscal Sustainability in Local Governments: Findings from Systematic Literature Review - Damong, Glorina C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The study examines the impact of digitalization on fiscal sustainability in local governments to assess how digital tools influence revenue mobilization, public service efficiency, and governance transparency. A systematic literature review was conducted, focusing on 17 peer-reviewed empirical studies published between 2015 and 2025. Employing the PRISMA framework, the review synthesizes quantitative, qualitative and mixed methods studies. Key findings reveal that digitalization, particularly through e-tax systems, increases tax compliance, streamlines service delivery, and reduces corruption. Commonly reported digitalization efforts include electronic tax filing systems, and smart governance platforms. Despite these advancements, several challenges persist such as limited technological infrastructure, data security risks, institutional resistance and low digital literacy, especially in developing rural areas. A major research gap identified is the limited exploration of long-term fiscal impacts and digital inclusion. These gaps are largely due to the absence of longitudinal studies and the underrepresentation of low-income or geographically remote municipalities in existing research. To address these limitations, the study recommends further investment in digital infrastructure, strengthening of cybersecurity frameworks, and expansion of digital literacy initiatives. Future research could focus on cross-country comparisons, environmental implications of digitalization, and long-term fiscal effects to inform more inclusive and resilient local governance strategies.